2016
DOI: 10.1080/10641955.2016.1218505
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis, elevated liver enzymes, and low platelet syndrome: Outcomes for patients admitted to intensive care at a tertiary referral hospital

Abstract: DIC is a major risk factor for maternal outcome among patients with HELLP syndrome who require intensive care. Low platelet count; high AST, ALT, LDH, INR; and total bilirubin are associated with high mortality risk in this patient group. In addition, low platelet count; low fibrinogen level; prolonged activated thromboplastin time; high INR; and high total bilirubin, LDH, blood urea nitrogen, and creatinine are associated with high risk for complications in this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
0
25
0
4
Order By: Relevance
“…The incidence rate rises to 10-20% for women with preeclampsia (Karumanchi et al, 2005) and to as high as 27.6% for women with eclampsia (Vigil-De Gracia et al, 2015). As a result, a stunning increase in the incidence rate of maternal and perinatal mortality and morbidity was observed in these patients (Sibai et al, 1993;Erdemoglu et al, 2010;Gedik et al, 2017). HELLP syndrome was initially described by Weinstein (1982) and its diagnosis is based on the laboratory analysis of microangiopathic hemolytic anemia, increased levels of liver enzymes, and thrombocytopenia in patients demonstrating symptoms of preeclampsia (Gasem et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence rate rises to 10-20% for women with preeclampsia (Karumanchi et al, 2005) and to as high as 27.6% for women with eclampsia (Vigil-De Gracia et al, 2015). As a result, a stunning increase in the incidence rate of maternal and perinatal mortality and morbidity was observed in these patients (Sibai et al, 1993;Erdemoglu et al, 2010;Gedik et al, 2017). HELLP syndrome was initially described by Weinstein (1982) and its diagnosis is based on the laboratory analysis of microangiopathic hemolytic anemia, increased levels of liver enzymes, and thrombocytopenia in patients demonstrating symptoms of preeclampsia (Gasem et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal and perinatal complications are frequently observed in patients with this syndrome. Mortality among women with HELLP syndrome was linked with low platelet count, low fibrinogen level, high INR value, and high serum levels of AST, ALT, and LDH, and complications in this patient group are associated with maternal death [27]. A study reported that 30% of patients with HELLP syndrome required mechanical ventilation in the ICU [28].…”
Section: Discussionmentioning
confidence: 99%
“…El diagnóstico de hemólisis se establece mediante biometría hemática y pruebas de funcionamiento hepático (35)(36)(37), en las que se encuentra una disminución de los valores de hematocrito (normal 80-120mg/dl), hematíes fragmentados (esquistocitos), aumento en la deshidrogenasa láctica (DHL) (normal 600U/l), y la bilirrubina >1,2 mg/dL (36,38).…”
Section: Diagnósticounclassified